Diagnosis of reading skill of students in the pre-admission course: an experience from Pré-SEED in Itabaiana, Sergipe State - doi: 10.4025/actascilangcult.v32i2.7327 - Freitag, Raquel Meister Ko (2010)
In this study we present the results of the application of an assessment about the reading skills, based on PISA test. This instrument was applied to the students in the pre-admission course offered by the Secretaria de Estado da Educação de Sergipe (Pré-Universitário SEED), in Itabaiana municipality, Sergipe state. Our results are according to PISA findings, evidencing that students in pre-admission course, are not proficient readers